THE ROLE OF SOCIAL MEDIA ON MARKET ACCESSIBILITY AND THE BUSINESS SUCCESS OF FISH CRACKERS INDUSTRY AT SERUYAN REGANCY - Permadi, Rokhman; Winarti, Lili (Universitas Muhammadiyah Jember, 2019)
Indonesia and in other developing countries. ICT has the ability to cut space and time limitations, especially access to communication and information, which has been a constraint to weak market access for entrepreneurs. One form of information technology that is developing and the current trend is the presence of social media (social media) that were built with the aim of connecting various people through internet media in various places without constraints of space and time. This study aims 1) to analyze the influence of social media as a marketing medium on the accessibility of fish cracker processing industries in Seruyan Hilir District, Seruyan Regency to the market. 2) analyze the relationship between market accessibility and business success. Respondents were taken from the region which is the center of fish cracker processing industry in Seruyan Regency, namely Seruyan Hilir Sub-district using the census method as many as 18 respondents. The analysis uses a partial structural equation model (PLS-SEM) with the main variables namely the use of social media, market accessibility, and business success. Each variable is then measured using several indicators. Based on the results of the analysis it is known that the use of social media has a significant effect on the accessibility of the fish cracker processing industry to the market. The business success is also significantly influenced by the accessibility of the fish cracker processing industry to the market